2015
DOI: 10.4103/2347-8659.160856
|View full text |Cite
|
Sign up to set email alerts
|

Neurocysticercosis in Nepal: a retrospective clinical analysis

Abstract: We retrospectively analyzed all the available data of NCC patients who were admitted to Neurology Department, Bir Hospital, Kathmandu, Nepal from April 2012 to February 2014. Computer tomography and magnetic resonance imaging (CT and MRI) head were used to classify the various stages of NCC. [8]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…14 In a study done at Bir hospital, Kathmandu, Out of 131 seizure patients admitted, 21 patients were diagnosed with NCC (16%). 15 In the study, mean age of the patients was 33.95 years, with 71.4% male patients and 28.6% female patients. The proportion of male patient was also high compared to female patients in our study too.…”
Section: Discussionmentioning
confidence: 88%
“…14 In a study done at Bir hospital, Kathmandu, Out of 131 seizure patients admitted, 21 patients were diagnosed with NCC (16%). 15 In the study, mean age of the patients was 33.95 years, with 71.4% male patients and 28.6% female patients. The proportion of male patient was also high compared to female patients in our study too.…”
Section: Discussionmentioning
confidence: 88%
“…Pork farming is strictly prohibited, and pork is not consumed at all due to the Islamic culture. The total population of Kuwait in 2019 included~1.3 million citizens who employed >650,000 domestic workers and babysitters mainly originating from India, Sri Lanka, Nepal, the Philippines, and Ethiopia, which are endemic for T. solium taeniasis [3,4,36,55] and could, therefore, pose a possible risk of infection transmission to the local Kuwaiti population through the fecal-oral route. This is also supported by a recent study that screened 500 newly arrived domestic workers and found 4.8% of these workers to have high levels of anti-T. solium taeniasis-specific IgG antibodies [28].…”
Section: Discussionmentioning
confidence: 99%
“…10,13 Furthermore, our data showed higher number of male patients with NCC that is consistent with the previous report. 5,6 All patients disclosed the eating habit of raw vegetables directly from the agricultural field and even without washing that could be the reason for cause of NCC in the patients of COMS-TH.…”
Section: Discussionmentioning
confidence: 99%
“…4 The prevalence of NCC in patients with seizure in mean age group of 33.9±16.4 was 16% (21 out of 131). 5 However, in children inconsistent prevalence of NCC was observed between 16.9% (229 out of 1355) 6 and 43% (72 out of 168). 7 In the present study, we reported the prevalence of NCC in seizure patients and association of NCC with dietary habits, in which pork eater are not directly linked.…”
Section: Introductionmentioning
confidence: 97%